Ethical patient care : a casebook for geriatric health care teams - Mezey, Mathy Doval (Johns Hopkins University Press, 2002)
This book is designed to teach effective and responsible group decision making to clinicians working in teams to treat older patients. The editors use case studies to present ethical dilemmas that team members encounter.